The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.jhsa.2009.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes in the Carpus During Finger Trap Distraction

Abstract: Introduction Wrist distraction is a common treatment maneuver used clinically for the reduction of distal radial fractures and mid-carpal dislocations. Wrist distraction is also required during wrist arthroscopy to access the radiocarpal joint and has been used as a test for scapholunate ligament injury. However, the effect of a distraction load on the normal wrist has not been well studied. The purpose of this study was to measure the 3-D conformational changes of the carpal bones in the normal wrist as a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
1
13
0
1
Order By: Relevance
“…They used a heavier traction of 10 kg, without noting complications. In concordance with carpal ligaments anatomy, joint space widening was more pronounced in the midcarpal and radiocarpal joints than in the metacarpophalangeal joints (18). Thus, further studies are needed to optimize this technique, notably by adapting the load to the gender and age of the patient.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…They used a heavier traction of 10 kg, without noting complications. In concordance with carpal ligaments anatomy, joint space widening was more pronounced in the midcarpal and radiocarpal joints than in the metacarpophalangeal joints (18). Thus, further studies are needed to optimize this technique, notably by adapting the load to the gender and age of the patient.…”
Section: Discussionmentioning
confidence: 79%
“…Based on our prior experience (institutional unpublished data), we set the traction at 3 kg in order to reduce the risk of traction-related adverse effects. In a recently published study on MDCT, Leventhal et al (18) similarly found substantial distractions in the radiocarpal and midcarpal joints with axial traction. They used a heavier traction of 10 kg, without noting complications.…”
Section: Discussionmentioning
confidence: 91%
“…The finger traps were then clipped to the freely hanging traction weight using a non-elastic cord routed over the edge of the MR gantry table (Figure 2). 24,25 The traction weight used was 7 kg for males and 5 kg for females. MR examination of the elbow was then repeated (Table 1).…”
Section: Ultrasound-guided Contrast Injectionmentioning
confidence: 99%
“…MRA with axial traction has been evaluated with success in the shoulder, [11][12][13] hip, [14][15][16][17][18][19][20][21] knee, 22 wrist, [23][24][25][26][27][28][29][30] ankle 31,32 and metatarsophalangeal 33 and metacarpophalangeal joints. 34 To the best of our knowledge, there is no study comparing MRA of the elbow with and without traction.…”
Section: Introductionmentioning
confidence: 99%
“….例えば,手根中央関節を効果的に他動運動させるリハビリテーション として,ダーツを投じるように手関節を橈背屈から掌尺屈へ運動させる,ダーツスロー運動の応用が検討されて いる (Werner, et al, 2004) (Guntern, et al, 2011) ( Leventhal, et al, 2010).野中らは牽引により関節骨間の開大が骨折部への 負荷を軽減しているのではないかと推測しているが,詳細は明らかにされていない(野中他,2010). 牽引による手関節の拘縮改善効果を検討するためには,手関節骨間の距離だけでなく,牽引下における各関節 の運動を明らかにする必要がある.しかし,牽引した状態における手関節の動態を測定し,その運動を考察した 例はきわめて少ない.Ishikawa らは屍体を用いた実験により,牽引が手関節の掌背屈運動に与える影響について 調査し,牽引を加えた場合,手関節骨部は非牽引時とは異なる挙動を示すことを確認した (Ishikawa, et al, 1999) Tanaka, Ikegami, Tsuchida, Sanada, Nishimura, Tada, Kawashima and Horie, Transactions of the JSME (in Japanese), Vol.81, No.824 (2015) は前腕側によって 2 種類に分類され, 手先側の 1:大菱形骨(Trapezium), 2:小菱形骨(Trapezoid), 3:有頭骨(Capitate) および 4:有鈎骨(Hamate)の 4 つを遠位列手根骨,前腕側の 5:舟状骨(Scaphoid),6:月状骨(Lunate),7:三角骨 (Triquetrum)および 8:豆状骨(Pisiform)の 4 つを近位列手根骨と呼ぶ.…”
unclassified